English grammar in use : supplementary exercises : with answers - Hashemi, Louise; Murphy, Raymond, 1946- (Cambridge University Press, 2012)
Cvičebnice obsahuje 200 cvičení z anglické gramatiky s klíčem. Je vhodná pro středně pokročilé a pokročilé studenty.
"To accompany English grammar in use, fourth edition"
Keywords: angličtina; mluvnice; English language; grammar; učebnice; diktáty a cvičení; textbooks; language exercises and dictations